The Influence of Work-Life Balance on Generation Z Employee Performance with Job Satisfaction and Compensation as Mediators - Putra, Rahmadani; Kalis , Maria Christiana Iman; Fahruna, Yulyanti; Mayasari , Endah (Jurnal Multidisiplin, 2025)
This study aims to analyze the influence of work-life balance on the performance of Generation Z employees working in coffee shops in Pontianak, by considering the role of job satisfaction and compensation as mediating variables. A quantitative approach was employed. Data were collected through an online questionnaire measured using a 5-point Likert scale. The respondents consisted of 170 coffee shop employees in Pontianak aged between 18 and 28 years, selected through purposive sampling. Data analysis was conducted using the SEM-PLS method with the SmartPLS 4 software. The results indicate that work-life balance has a positive and significant effect on employee performance. Work-life balance also has a positive and significant impact on job satisfaction, as well as on compensation. Furthermore, job satisfaction has a positive and significant effect on employee performance. Likewise, compensation also positively and significantly affects employee performance. Both job satisfaction and compensation successfully mediate the relationship between work-life balance and employee performance.